2016
DOI: 10.1007/s13224-016-0915-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intravenous Tranexamic Acid on Caesarean Blood Loss: A Prospective Randomised Study

Abstract: Background Post-partum haemorrhage (PPH) is a major cause of maternal mortality globally. Tranexamic acid, an anti-fibrinolytic agent, is a novel approach in an attempt to prevent this dreadful complication. This study aims to document the efficacy of intravenous (IV) tranexamic acid in reducing blood loss during and after caesarean section (CS). Methods In this prospective randomised placebo-controlled open-label study, 100 mothers scheduled for elective CS were randomly selected and divided into two groups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…A recent meta‐analysis of nine trials involving 2365 patients confirmed these findings, demonstrating that the administration of tranexamic acid before cesarean delivery significantly reduces intra‐ and postoperative blood loss and blood transfusion with no increase in thromboembolic events . After this analysis, three more placebo‐controlled trials have shown that tranexamic acid administration immediately before cesarean delivery significantly reduces reported intraoperative blood loss and postoperative declines in hemoglobin without any increase in adverse maternal or neonatal effects …”
Section: Intraoperative Considerationsmentioning
confidence: 86%
See 1 more Smart Citation
“…A recent meta‐analysis of nine trials involving 2365 patients confirmed these findings, demonstrating that the administration of tranexamic acid before cesarean delivery significantly reduces intra‐ and postoperative blood loss and blood transfusion with no increase in thromboembolic events . After this analysis, three more placebo‐controlled trials have shown that tranexamic acid administration immediately before cesarean delivery significantly reduces reported intraoperative blood loss and postoperative declines in hemoglobin without any increase in adverse maternal or neonatal effects …”
Section: Intraoperative Considerationsmentioning
confidence: 86%
“…48 After this analysis, three more placebocontrolled trials have shown that tranexamic acid administration immediately before cesarean delivery significantly reduces reported intraoperative blood loss and postoperative declines in hemoglobin without any increase in adverse maternal or neonatal effects. [49][50][51] No trials have specifically examined the role of tranexamic acid in the surgical management of PAS disorders. However, the quality of the evidence on postpartum hemorrhage justifies its use in the management of women diagnosed prenatally or presenting with PAS disorders at the time of delivery.…”
Section: Tranexemic Acidmentioning
confidence: 99%
“…Seven trial registrations without sufficient data for analysis were also excluded. Finally, 21 studies (19 research papers and 2 conference abstracts) with 3852 patients were eligible for our analysis. Figure shows the details of study selection and inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is still a controversy about the prophylactic application of TXA to patients undergoing CS. Thus, we identified all available randomized controlled trials (RCT), totally 21, to evaluate whether preoperative administration of TXA has potential effects on reducing blood loss as well as transfusion requirements for patients undergoing CS. Moreover, we also investigated the impact of TXA on other factors associated with bleeding, including hemoglobin and hematocrit drops, additional uterotonic agent use (oxytocin and methylergometrine) and massive hemorrhage rate.…”
Section: Introductionmentioning
confidence: 99%
“…6 TXA has also been studied extensively to reduce blood loss in and after CS. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Intravenous TXA is a synthetic derivative of the amino acid lysine that exerts its antifibrinolytic effect through the reversible blockade of lysine binding site on plasminogen molecules. Adverse drug reaction of TXA are nausea, headache, and thromosis.…”
Section: Introductionmentioning
confidence: 99%